2021
DOI: 10.1016/j.psj.2020.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of riboflavin and Bacillus subtilis on internal organ development and intestinal health of Ross 708 male broilers with or without coccidial challenge

Abstract: In a companion study, we found that inclusion of different doses of riboflavin affected growth performance of Ross 708 male broilers' responses to coccidial challenge (by 5 Eimeria spp on day 14 of age) and dietary Bacillus subtilis ( B. subtilis ) supplementation. The current study was conducted to further test whether supplementation of B. subtilis and riboflavin will reduce negative impact and inflammation caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Male broilers are more susceptible to WB due to their biological characteristics related to higher body weight, fat metabolism, and oxidative stress response ( Brothers et al, 2019 ). Antibiotics (bacitracin), probiotics ( Bacillus subtilis ), and cocci challenges influence gut health conditions, which can affect internal organ development ( Wang et al, 2018 ; Poudel et al, 2021 ). Dietary antibiotics can modify organ size and function, thus improving growth performance ( Castanon, 2007 ; Crisol-Martinez et al, 2017 ; Manafi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Male broilers are more susceptible to WB due to their biological characteristics related to higher body weight, fat metabolism, and oxidative stress response ( Brothers et al, 2019 ). Antibiotics (bacitracin), probiotics ( Bacillus subtilis ), and cocci challenges influence gut health conditions, which can affect internal organ development ( Wang et al, 2018 ; Poudel et al, 2021 ). Dietary antibiotics can modify organ size and function, thus improving growth performance ( Castanon, 2007 ; Crisol-Martinez et al, 2017 ; Manafi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was intestinal inflammation in d 27, which was in the path of the recovery until d 36. Since the birds were on the path of recovery, we did not observe any changes in jejunum histology on d 36 in a companion study [ 39 ] and challenge birds, had lower FCR d 28 to 35 compared to non-challenged. The lower in FCR of challenged birds from d 28 to 35 in this study; might be due to challenged birds still having a lower BW, and the nutritional requirement for maintenance was lower than that of the heavier non-challenged birds for the same period.…”
Section: Discussionmentioning
confidence: 86%
“…In a companion study, we found that the Eimeria spp. challenge reduced villus height to crypt depth ratio and increased crypt depth in duodenum and ileum on d 27 [ 39 ]. The damage in the intestinal structure due to Eimeria proliferation can reduce absorption of carbohydrates and protein, as it was found that Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the inclusion of subtherapeutic dosages of antibiotics as a growth promoter in poultry diet improved the growth, production, and feed efficiency by reducing the pathogens ( Clostridium spp., Salmonella spp., Escherichia coli , etc.) in the gastrointestinal tract and enhancing gut health [ 5 , 6 , 7 , 8 ]. Although the inclusion of subtherapeutic dosages of antibiotics in poultry diets has some beneficial effects, its use has been questioned, mostly due to the antimicrobial resistance among zoonotic microorganisms and antibiotic residues in the final products [ 1 , 3 , 9 ].…”
Section: Introductionmentioning
confidence: 99%